Program Self-Care Pada Penderita Diabetes Mellitus Di Wilayah Puskesmas Sibela - Rizqy Febriansyah; Tiara Fatmarizka; Anis Dwi Charisa (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Introduction: Mojosongo Village is one of the Villages in Jebres District, Surakarta. Diabetes Mellitus is a non-communicable disease which is one of the challenges in the development of the health sector, where the majority of people exposed to it are of productive age. The method used is to provide counseling in the form of self-care management for diabetes mellitus patients to the community in the working area of the Sibela Community Health Center, Mojosongo Village. Objective: The aim of the physiotherapy program in cases of diabetes mellitus is education and demonstration of self-care management to control the incidence of diabetes mellitus Results: It is hoped that the results of this Community Service activity will become a reference for physiotherapists and other health professions so that similar activities can be carried out, so that The benefits can improve public health, especially in cases of diabetes mellitus.